Changes in mitochondrial function and mitochondria associated protein expression in response to 2-weeks of high intensity interval training - Vincent, Grace; Lamon, Severine; Gant, Nicholas; Vincent, Peter; MacDonald, Julia; Markworth, James; Edge, Johann; Hickey, Anthony (Frontiers in Physiology, 2015)
Purpose: High-intensity short-duration interval training (HIT) stimulates functional and metabolic adaptation in skeletal muscle, but the influence of HIT on mitochondrial function remains poorly studied in humans. Mitochondrial metabolism, as well as mitochondrial-associated protein expression were tested in untrained participants performing HIT over a two-week period. Methods: Eight males performed a single-leg cycling protocol (12 x 1 min intervals at 120% peak power output, 90 s recovery, 4 days/week). Muscle biopsies (vastus lateralis) were taken pre- and post-HIT. Mitochondrial respiration in permeabilized fibres, citrate synthase (CS) activity and protein expression of peroxisome proliferator-activated receptor gamma coactivator (PGC-1α) and respiratory complex components were measured. Results: HIT training improved peak power and time to fatigue. Increases in absolute oxidative phosphorylation (OXPHOS) capacities and CS activity were observed, but not in the ratio of CCO to the electron transport system (CCO/ETS), the respiratory control ratios (RCR-1 and RCR-2) or mitochondrial-associated protein expression. Specific increases in OXPHOS flux were not apparent after normalization to CS, indicating that gross changes mainly resulted from increased mitochondrial mass. Conclusion: Over only 2 weeks HIT significantly increased mitochondrial function in skeletal muscle independently of detectable changes in mitochondrial-associated and mitogenic protein expression.